Hollywood Hills [compact disc, unabridged] : a novel - Wambaugh, Joseph (Hachette Audio, 2010)
A circle of teenage burglars that the media has dubbed The Bling Ring has taken to pillaging the homes of Hollywood celebutants, and when a pair of drug-addled young copycats stumbles upon an art heist, that's just the beginning of the disaster to come. Soon LAPD veteran "Hollywood Nate" Weiss, surfer cops Flotsam and Jetsam, and the rest of the team at Hollywood Station have a deadly situation on their hands.